1989
DOI: 10.1007/bf00687754
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of necrotizing myelopathy associated with malignancy caused by herpes simplex virus type 2

Abstract: Two cases of necrotizing myelopathy were autopsied; one was complicated with lung carcinoma and the other with chronic type adult T cell leukemia (ATL leukemia). To our knowledge, they were the first cases of their type in Japan. In both cases, necrosis of the spinal cord was observed in the gray and white matter along most of its extent. Marked changes were found in the lumbar segment. The patients were not treated with intravenous cancer chemotherapy or irradiation. Immunohistochemical and electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…In previous reports, HSV myelitis was accompanied by conditions that reduce immunologic competence, such as acquired immunodeficiency syndrome [5,6], malignancies [7,8], and diabetes mellitus [3]. Ellie et al [12] and Flope et al [13] have recently reported HSV myelitis in nonimmunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, HSV myelitis was accompanied by conditions that reduce immunologic competence, such as acquired immunodeficiency syndrome [5,6], malignancies [7,8], and diabetes mellitus [3]. Ellie et al [12] and Flope et al [13] have recently reported HSV myelitis in nonimmunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Indeed, previous reports have shown that some ATL patients are infected with these 2 pathogens. 24,25 Using these 2 infection models, we demonstrated that sHBZ suppresses cell-mediated immunity. Furthermore, we determined the molecular mechanism of this HBZ-mediated immune suppression.…”
Section: Introductionmentioning
confidence: 94%
“…Neuropathological findings in herpes virus associated necrotizing myeloradiculitis include extensive necrotic and hemorrhagic changes associated with necrotizing vasculitis and perivascular lymphocytic infiltration involving both gray and white matter as well as spinal roots 10,14 .…”
Section: Discussionmentioning
confidence: 99%